2013
DOI: 10.7732/kjpr.2013.26.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effect of Extracts from Folk Plants in Ulleung Island

Abstract: -We investigated the effect of extracts(50 µg/mL) from 31 folk plants in Ulleung Island on nitric oxide(NO) production in lipopolysaccharide (LPS)-stimulated RAW264.7 cells. Actinidia arguta(leaf, twig), Hovenia dulcis(leaf), Camellia japonica(leaf, twig), Sambucus sieboldiana var. pendula(leaf, twig) and Fallopia sachalinensis(root) showed significant NO inhibition activity(42%~88% NO inhibition rate). Of them, we selected 3 samples (A. arguta, H. dulcis and C. japonica) showing more than 50% NO inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…The study of methanolic extracts of L . lancifolium bulbs, on NO inhibition, in LPS‐treated RAW 264.7 cells (Kim et al, 2013) showed 21.93 ± 4.68% of NO inhibition at a concentration of 50 µg/ml; thus, the effect on NO inhibition of bulbs of this study could be considered.…”
Section: Resultsmentioning
confidence: 63%
“…The study of methanolic extracts of L . lancifolium bulbs, on NO inhibition, in LPS‐treated RAW 264.7 cells (Kim et al, 2013) showed 21.93 ± 4.68% of NO inhibition at a concentration of 50 µg/ml; thus, the effect on NO inhibition of bulbs of this study could be considered.…”
Section: Resultsmentioning
confidence: 63%
“…위 약물들은 여드름 형성 억제를 위해 정도의 차이는 있지만 강력한 면포 용해 기능을 가지고 있고 여 드름 균의 증식을 억제하며 염증반응을 완화 시키는 효능이 있어 치료효과를 증진시킨다 . 그러나 이 약물들은 장기간 사용 했을 때 피부자극과 건조함, 홍조, 가려움의 부작용 (Kim & Lee, 2009;Suh et al, 2016 (Kim et al, 2013), 항산화와 항암효과가 나타났다 (Kim et al, 2010b).…”
Section: 최근에는 4가지 원인 외에 피부장벽 이상에 의하여 여드름이unclassified
“…The increase in dietary antioxidant intakes may help to support the limiting antioxidant concentrate and also promote the normal functioning of physiological systems [ 20 ]. The potential of the extracts from indigenous Korean plants to scavenge these free radicals and modulate inflammatory reactions has been demonstrated [ 21 , 22 , 23 ]. Additionally, many researchers have used the antioxidant activity assay to reveal the beneficial effect of different plant extracts [ 24 ].…”
Section: Introductionmentioning
confidence: 99%